Fictional Representations of Antarctic Tourism and Climate Change: To the Ends of the World - Nielsen, H (Brill, 2022)
Antarctica is sliced off the bottom of most Mercator maps, with the southern latitudes banished beyond the margins. Yet the continent is home to a thriving tourism industry, with over 50,000 people heading south for leisure each summer season. As Elizabeth Leane puts it, Antarctica, which for centuries has for most people functioned primarily as a symbol, is now an expensive but nonetheless feasible travel destination. Promoted through tourism, Antarctica has become a commodity in its own right. And yet, when it comes to climate change, Antarctic tourism raises a paradox: by carrying people to view the regions that are affected by anthropogenic warming, ships actively contribute to further greenhouse gas emissions. These emissions in turn have global effects, leading to ocean acidification, warming average temperatures, disruption of sea ice formation and sea level rise. In seeking to experience untouched wilderness, tourists are helping to bring about its demise. Authors such as Bulgarian-German writer and translator Ilija Trojanow (born 1965) have explored these complex relationships between humans, ice and travel in their fiction. Trojanows novel The Lamentations of Zeno (2011) re-centres Antarctica. It invites readers to see the continent as part of wider global systems of labour, power, and climate, and to reflect ecocritically on their own relationship with the ice at the ends of the earth.